Radiological Features in Deceased COVID-19 Patients at a Hospital in Bandung - Setiapriagung, D.; Tresnasari , C.; Widiyanto, T.; Yulianto , F. A.; Respati , T.; Yuniarti, L. (KnE Life Sciences, 2022)
COVID-19 attacks the respiratory system, especially the lung. Therefore, it is necessary to examine the lung radiology of COVID-19 patients to plan the best treatment. This study aimed to describe radiological features in deceased patients at a hospital in Bandung, Indonesia. This study uses secondary data from the medical records of deceased COVID-19 patients from December 2020 to February 2021. Amongst the 129 patients who died whilst hospitalized, their chest X-ray showed pneumonia consisting of ground glass opacities (GGO) and consolidated lesions. The mean distribution of lesions was unilateral in 3 (2.33%) and bilateral in 126 (97.67%). In comparison, peripheral lesions were found in 80 (62.02%), and peripheral-medial lesions were found in 49 (37.98%). The mean of the lesions affecting the upper lung fields were 2.63 (DS 1.19), the middle lung fields were 4.39 (DS 1.82), and the lower lung fields were 4.88 (DS 1.53). When admitted to the isolation ward, the average Brixia score on a chest X-ray was 11.9 (95% CI 12.74; 11.16). In conclusion, the radiological features of COVID-19 patients who died under treatment showed ground glass opacities and consolidated lesions. The predominant distribution was on bilateral, peripheral, and lower lesions with a high Brixia score. Keywords: COVID-19, mortality, the brixia score.